2021
DOI: 10.1097/md.0000000000027563
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HIV non-occupational post-exposure prophylaxis for men who have sex with men in 2 cities of Southwestern China

Abstract: Non-occupational post-exposure prophylaxis (nPEP) has often relied on the joint work of emergency physicians and infectious disease specialists in busy emergency departments and human immunodeficiency virus (HIV)/sexually transmitted infections clinics abroad, where adherence education and follow-up are invariably reactive. In our pilot study, community-based organizations (CBOs) were invited to together implement the nPEP tailored to men who have sex with men (MSM) in 2 cities of Guangxi in Southwestern China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
(117 reference statements)
1
3
2
Order By: Relevance
“…Another reason for the high preponderance of females may also be due to better female healthcare-seeking behaviours. [20] This finding is similar to that reported from Nigeria and Yaoundé, Cameroon, which belongs to the same geographical spread of West Africa. [9, 18,19] In contrast to the present study, Western countries show male predominance among those seeking nPEP, [16,21] probably because most of the patients in the western studies were men who have sex with men (MSM).…”
Section: Discussionsupporting
confidence: 88%
“…Another reason for the high preponderance of females may also be due to better female healthcare-seeking behaviours. [20] This finding is similar to that reported from Nigeria and Yaoundé, Cameroon, which belongs to the same geographical spread of West Africa. [9, 18,19] In contrast to the present study, Western countries show male predominance among those seeking nPEP, [16,21] probably because most of the patients in the western studies were men who have sex with men (MSM).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, 97.0% (523/539) of PEP users presumably completed the full 28-day course of medication, and this rate was higher than the completion rates in 2 other Chinese studies, where 86% [47] and 92.2% [41] of PEP users completed the 28-day course of medication, respectively. Furthermore, a systematic review and meta-analysis of 97 studies worldwide showed an even lower rate of PEP completion (67.2%; 95% CI 59.5%-74.9%) [48].…”
Section: Principal Findingscontrasting
confidence: 69%
“…Over one-quarter of PEP users in this study reported prior PrEP usage, which was higher than that indicated by current limited data (12.1%) [41]. The reasons for this might include higher health awareness or more convenient access to HIV preventative services via the internet medical platform.…”
Section: Principal Findingscontrasting
confidence: 67%
See 1 more Smart Citation
“…PrEP and PEP are highly validated HIV prevention tools and are part of a wide range of prevention measures, including HIV testing, condom use, and screening and treatment for sexually transmitted infections ( 55 ). We should train community physicians in risk assessment, medication adherence assessment, and offline communication through online social media and offline posters, cards and brochures to promote PEP knowledge and inform them of ways to seek services ( 56 ). The completion and use of PEP has been shown to vary depending on the drug regimen.…”
Section: Discussionmentioning
confidence: 99%